THE BIODIVERSITY OF NURSERY GROUND IN SWAMP AREAS IMPORTANT TO SURVIVE THE BLACK FISHES IN THE WETLAND - Sagala, Effendi Parlindungan (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2015)
Fish nursery grounds are important for the life cycle of fishes and often these areas are not particularly well studied or the processes understood in Sumatra. On December 2014, The blackfishes in swamp ecosystem of South Sumatera consist of Channa striata, Clarias batrachus, Anabas testudineus, Trichogaster trichoterus, Polyacanthus hasselti, Rasbora argyrotaenia, Betta taeniata, Betta anabantoides, Monopterus albus, Notopterus notopterus,Â Trichogaster pectoralis, Trichogaster leeri, Oxyeleotris marmorata and Helostoma temmincki.. This observation is constitute first record of blackfishes in Sumatra.Â Keywords: First, nursery grounds, blackfishes, observation, sumatra.